Many lives, many masters eaudiobook The true story of a prominent psychiatrist, his young patient, and the past-life therapy that changed both their lives. - Weiss, Brian L. (Simon & Schuster Audio, 2021)
From author and psychotherapist Dr. Brian Weiss comes the classic New York Times bestseller on the true case of the past-life therapy that changed the lives of both the prominent psychiatrist and young patient involved—now featuring a new afterword by the author. As a traditional psychotherapist, Dr. Brian Weiss was astonished and skeptical when one of his patients began recalling past-life traumas that seemed to hold the key to her recurring nightmares and anxiety attacks. His skepticism was eroded, however, when she began to channel messages from the "space between lives," which contained remarkable revelations about Dr. Weiss' family and his dead son. Using past-life therapy, he was able to cure the patient and embark on a new, more meaningful phase of his own career. With more than one million copies in print, Many Lives, Many Masters is one of the breakthrough texts in alternative psychotherapy and remains as provocative and timeless as it was when first published.